Pisa syndrome associated with mirtazapine: a case report - Yuji Yamada; Harumasa Takano; Maki Yamada; Naoko Satake; Naotsugu Hirabayashi; Mitsutoshi Okazaki; Kazuyuki Nakagome (BMC, 2018)
Abstract Background Mirtazapine is a noradrenergic and specific serotonergic antidepressant; its pharmacological profile indicates a low risk for dopaminergic adverse effects. To date, there has been only a single case report of Pisa syndrome associated with mirtazapine. Case presentation The authors report a case involving a 79-year-old woman with bipolar disorder, in whom Pisa syndrome occurred after introduction of mirtazapine, and completely disappeared 3 days after suspension of the drug. Conclusions Aspects of this particular case suggest that Pisa syndrome is a possible side effect of Mirtazapine.